Analysis Of Nutritional Content And Organoleptic Quality Of Biscuits Substituting Green Bean Flour (Vigna Radiata) And Carrot Flour (Daucus Carota L.) As A High-Protein Snack For Breastfeeding Mothers - Dian Nafies; Idcha Kusma Ristanti; Nikita Welandha Prasiwi (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Introduction. Exclusive breast milk (ASI) is breast milk given to babies from birth for 6 months without adding or replacing it with other foods and drinks except medicines, vitamins, and minerals. Breastfeeding is crucial because it is related to conditions of undernutrition and overnutrition. However, exclusive breastfeeding is not easy to do because some mothers complain that there is not enough breast milk. The solution to this problem is making high-protein foods or snacks to help increase breast milk production and maintain the quality of the mother's breast milk. One ingredient that is high in protein is green beans and carrots. So, to meet protein needs, you can make biscuits instead of green bean flour and carrot flour as an alternative snack for breastfeeding mothers. Research Objectives: This research aims to find out the effect of the substitution of green bean flour and carrot flour on the protein content and organoleptic quality of high-protein biscuits. Metode. This research used a True Experimental Design with a Completely Randomized Design (CRD), 4 treatment levels and 6 replications. The treatment applied was the ratio of wheat flour, green bean flour, and carrot flour in each treatment, namely P0 (100:0:0), P1 (70:20:10), P2 (60:10:30), P3 ( 50:30:20). Result&Analysis. The results showed that there was an effect of increasing the protein content in biscuits by substituting green bean flour and carrot flour, the highest value was found in the P3 treatment. The presence of a significant influence on the color, flavor, smell, and texture of the biscuits was demonstrated using the Kruskal Wallis Test (p<0.005) and continued with the Mann-Whitney test if it showed differences in all treatments. The best treatment is in the P1 treatment biscuit. Discussion. This research concludes that biscuits substituted for green bean flour and carrot flour influence nutrient levels, protein, and organoleptic quality. This research concludes that substitute biscuits for green bean flour and carrot flour influence protein content and organoleptic quality. Keywords: Biscuits; Green Bean Flour; Carrot Flour; Protein; Organoleptic Quality.